The archaeology of large-scale manipulation of prey : the economic and social dynamics of mass hunting - Carlson, Kristen, 1980-; Bement, Leland C. (University Press of Colorado, 2018)
"Expands the understanding of large-scale hunting methods beyond the customary role of subsistence and survival to include the social and political realms where large-scale hunting adaptations evolved, primarily from the Americas and spanning from the Folsom Period on the Great Plains to the ethnographic present in Australia"--Provided by publisher